Polar Law Textbook (Copenhagen : Nordic Council of Ministers, 2010)
The idea for this textbook developed from the recognition of the need to disseminate information about Polar Law as an emerging field of legal studies - an area of study long overdue greater recognition. Developments in the Polar Regions - the Arctic and Antarctica - are now the subject of growing interest and importance. They concern a divergent range of global and regional development issues and beg further inquiry into the role of law in dealing with many of these issues. This textbook is the first educational material of its kind. It attempts to illustrate the importance of legal values in addressing various challenges across the Nordic region, among remote Arctic communities and globally. The textbook focuses on the various developments in international and domestic law concerning the Polar Regions (e.g., issues of environmental law, law of the sea, resources, human rights law and Indigenous peoples' rights, etc.). By looking at linkages between different areas of law and the other social sciences, the textbook also explores the relevant aspects of the economic, social and political developments affecting both Polar areas (e.g., questions of Polar governance, economics, and the political situation in some of the Arctic areas). The authors hope that this pioneering work will encourage anybody interested in Polar Law to pursue further studies, research or cooperation on the many initiatives which take place within the Nordic, Arctic and global community in relation not just to the Arctic but also to the Antarctic.